UPAYA DITRESNARKOBA POLDA KALTIM DIDALAM MENANGGULANGI PEREDARAN DAN PENYALAHGUNAAN NARKOBA DIKALANGAN PELAJAR - I Nyoman Suantara (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACT            The problem of drug abuse in Indonesia now is very alarming. This is due to several things, among others, because Indonesia is located in a position between three continents, and given the development of science and technology, the influence of globalization, highly developed transportation flows and shifting of materialistic values with the dynamics of illicit trafficking targets. Indonesian society and even the world community, in general, are currently facing a very alarming situation due to the rampant illegal use of various types of drugs. This concern is heightened due to the rampant drug trafficking which has spread in all walks of life, including among the younger generation. This will greatly affect the life of the nation and state in the future.            NAPZA (Narcotics, Psychotropics, and addictive substances) is a drug or material that is useful in the fields of medicine, health services, and scientific development, and on the other hand can cause very detrimental dependencies if used without control, strict and careful supervision. Drug abuse is a form of community ignorance that is a reflection of the weakness of human nature, such as in Indonesian society where many people do not understand the dangers of drug abuse.            Even more alarming is that Indonesia is not only an illegal drug marketing area but also a drug-producing area. The majority of victims of drug abuse are aged 15-20 years, ages who are supposed to be actively doing constructive activities, very productive ages.            Based on the background description of the problem above, there are 2 problems (1) What is the effort of the East Kalimantan Regional Police Directorate of Narcotics in Addressing Circulation and Drug Abuse Among Students? (2) What are the obstacles faced by the East Kalimantan Regional Police Directorate of Narcotics in Addressing Circulation and Drug Abuse Among Students?            So it can be concluded (1) The implementation of the East Kalimantan Regional Police countermeasures through preventive and repressive measures. Preventive action is carried out through campaigns, outreach, counseling, approaches with families, and so forth. These efforts are a form of prevention carried out institutionally or in collaboration with community participation. Campaigns, outreach, and outreach are priorities for the police so that repressive actions can be minimized. (2) Broadly speaking, the obstacles taken by the police occur in the limited human resources of infrastructure and communication interruptions. Dismissal of information from the public as a reporter also becomes an obstacle in efforts to tackle drug abuse among adolescents, it is necessary to provide further information to the public at large about the dangers of drugs and there is an encouragement for the public to dare to report in order to protect the nation's generation so that it does not fall further in drug abuse. Keywords: Drugs, Abuse, Countermeasures